1996
DOI: 10.1507/endocrj.43.375
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Localization of Activin A and Follistatin in Human Tissues.

Abstract: Abstract.We immunohistochemically investigated the localization of activin A and follistatin in various human tissues with specific antibodies to recombinant human (rh-) activin A and rh-follistatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
4

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 55 publications
2
49
4
Order By: Relevance
“…Studies have shown that mouse, rat and human pancreatic islet cells produce activin A and follistatin [23,24,29]. We also detected the activin βA subunit, activin type II receptors (actRII and actRIIB) and activin type I receptor (actRIB/alk4) in human islets (data not shown).…”
Section: Resultsmentioning
confidence: 60%
See 3 more Smart Citations
“…Studies have shown that mouse, rat and human pancreatic islet cells produce activin A and follistatin [23,24,29]. We also detected the activin βA subunit, activin type II receptors (actRII and actRIIB) and activin type I receptor (actRIB/alk4) in human islets (data not shown).…”
Section: Resultsmentioning
confidence: 60%
“…Conversely, follistatin completely reversed the dedifferentiating effects of activin A. Both activin A and follistatin are produced in islets [23,24], suggesting paracrine control of beta cell maturity. Interestingly, a preliminary experiment showed that levels of the activin βA subunit were increased in human islets treated with activin A (M. Szabat, unpublished data), supporting a positive feedback for autocrine or paracrine regulation of activin A expression.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…At the same time, primordial through to primary follicles do not express follistatin mRNA (Kogawa et al, 1991;Braw-Tal, 1994;Tisdall et al, 1994), implying that follistatin may not be involved in the initial stage of recruitment of follicles. Species differences occur, as the expression of follistatin is maintained in the corpus luteum in primates, whereas in other species, expression falls markedly after ovulation in the developing corpus luteum (Kogawa et al, 1991;Roberts et al, 1993;Wada et al, 1996).…”
Section: Location and Secretion Of Follistatinmentioning
confidence: 99%